Analisis Nilai Resistansi pada Konfigurasi Keypad Satu Kabel serta pemanfaatannya dalam media pembelajaran - Muharmen Suari (Universitas Islam Negeri Imam Bonjol Padang, 2019)
An analysis of resistance values has been carried out on a single cable keypad configuration using a voltage divider system. The single cable keypad configuration is used to minimize the use of a microcontroller input output line. Keypads can be arranged using a matrix and without a matrix. For without matrix the number of arduino input output paths used is as many as the number of buttons on the keypad while using the matrix the number of input output lines used is fewer, namely the number of rows and columns that make up the matrix keypad. The 3x4 matrix keypad will require 7 microcontroller input output lines. On a one-wire matrix keypad a voltage divider system is used by adjusting the resistance value of a resistor such that the voltage divider output will give a different value for each keypress keypad. For this reason, it is necessary to analyze what resistance value is needed in the matrix keypad configuration so that it is expected that it can be used for a larger matrix size if later in the making of learning media it requires a very large number of buttons.